Propagation of Surface Plasmon Waves along Multi Wall Carbon Nanotube with Gold Core (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the propagation of surface plasmon waves along multiwalled carbon  nanotube with gold core. We have modeled the shells of multiwalled carbon nanotube as  impedance sheets with axially directed surface conductivity incorporating inter shell coupling  in an integral equation approach. We have found that in low frequency regime optical  interband transitions did not occur and guided waves propagated with low attenuation in an  multiwalled carbon nanotube which has metallic shells. In the same frequency range the axial  polarizability of a finite length multiwalled carbon nanotube has a resonant behavior due the  antenna length matching effect. The shells with surface conductivity due to interband  transitions suppressed guided wave propagation. Surface Plasmon wave propagation in a  multiwalled carbon nanotube with gold core showed that in the near infrared and visible  regime the shells behaved as lossy dielectric materials and suppressed surface wave  propagation along the gold core. The electromagnetic characteristics of carbon nanotube  based antennas have been examined in different frequency regime ranging from the  microwave to the visible regime. Carbon nanotube has been demonstrated to play a crucial  role connected electrically to planner periodic structures of single wall carbon nanotubes,  carbon nanotube bundles and carbon nanotube arrays. The inter shells interaction leaded to  inter shell electron tunneling or hopping. Fermi momentum of two incommensurable shells  do not coincide within the first Brillouin zone and the inter shell tunneling vanished. In the  presence of localized defects inter shell conduction increased and defectfree shells were  managed by neglecting intershell conduction. We have used microscopic model for  multiwalled carbon nanotube and radiation characteristics were determined by its  waveguiding properties, the dispersion equation for guided wave propagation on an infinitely  long multiwall carbon nanotube. We have found that the guided wave has strong retardation  and high attenuation so that the frequency of a geometric resonance is not connected to the  free space wave length but to a shorter effective wavelength that depends on the material  properties. The obtained results were compared with the previously obtained results and were  found in good agreement.